An ad-hoc web of things service bus - Gramacho, Sergio; Prazeres, Cássio; Figueiredo, Gustavo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
The Web of Things (WoT) is a new trend related to the Internet that have yet to scale to mass usage. Consumer and in-vehicle contexts can promote WoT to mass usage. For these contexts, ad-hoc operation and complexity abstraction is very important. This paper suggests the creation of an ad-hoc service bus for the WoT. The solution uses Bonjour and Link-Local technologies to provide the main needed functions for a WoT RESTFul service bus operation. A proof of concept was executed to demonstrate this proposition's viability in a ah-hoc network without any infrastructure.